REALIZATION OF CROATIAN AGRICULTURAL POLICY GOALS: SELF-SUFFICIENCY AND AGRICULTURAL INCOME - Tihana KOVAČIĆEK; Mateja JEŽ ROGELJ; Ornella MIKUŠ; Tajana RADIĆ; Ramona FRANIĆ; Magdalena ZRAKIĆ SUŠAC (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The aim of this research is to determine the achievement of Croatian agricultural policy goals (AP) in the area of self-sufficiency and agricultural income. Previous studies do not provide specific quantitative estimates of the achievement of Croatian agricultural policy goals. Therefore, in this research self-sufficiency is considered achieved if 6 out of 11 selected products have an average self-sufficiency rate above 100%. Income, as AP goal, is considered achieved when agricultural income is lower than income from non-agricultural activities by up to 30%. In the analyzed period (from 1997 to 2020), the goal of self-sufficiency was not achieved. Considering that the income from agricultural activity is usually 30% lower than the income from non-agricultural activity, it can be concluded that the income goal has been achieved. Looking only at the statistics, without conducting empirical research, one can conclude that the Croatian agricultural policy is indeed "the most successful agricultural policy in the world". On the other hand, the same agricultural policy has not resulted in a competitive agricultural sector, developed rural areas, or sufficient production to meet the needs of the local population.